SME firms performance in Nigeria: Competitive advantage and its impact - Eniola, Anthony A.; Harry, Entebang (International Journal of Research Studies in Management, 2014)
Small and medium enterprises (SME) performance forms a very important part of the Nigerian economy. The SME sector is a major engine which encourages the growth of jobs and wealth creation in the country’s economic system. SMEs performance act as a significant part that is linked to the strengthening and enhancement of the development of the country. The SME performance and growth in manufacturing, agriculture, services, and so on, has been considered as the engine drive and has contributed to the Nigeria economy. Sustainable growth and the increase of SME performance, competitiveness will open numerous doors for employment opportunities, tangible and intangible assets (investment) in the environment. The SME sector has developed rapidly over these years. The major aim of this paper is to look into the SME sustainable competitive advantage and emphasis on its growing importance. Likewise, some guidelines were offered in order for SMEs to reach performance and competitive advantage. In a wider perspective, this paper would provide some available conclusions and concrete recommendations. Besides, this work will serve as an information cause that will promote and orient SMEs performance towards competitive advantage. Through this way, it will contribute to the continuous promotion and active growth of SMEs, as easily to increase the level of the firm’s performance and business competitiveness in Nigeria.